(untitled) (Applied Biological Research, 2025)
This ethnobotanical survey documents the indigenous medicinal plant knowledge of the Garo tribes in the Goalpara district of Assam (India), focusing on their traditional plant-based treatments for a variety of human and livestock ailments. Through interviews with 30 key informants, recognized as holders of traditional knowledge within their community, the study aimed to record this knowledge, contributing to the conservation and sustainable use of medicinal plant species in the region, and providing a foundation for evaluating their therapeutic properties. The survey revealed the use of 45 medicinal plant species from 27 families for treating various human and livestock ailments. Trees were the most common plant form (37.77%), followed by herbs (31.11%). Leaves were the most frequently used plant part for both human (48.88%) and animal (35.71%) treatments. Quantitative analysis showed high use-value (UV) indices for species like Azadirachta indica, Centella asiatica, Leucas aspera, Bergera koenigii, Terminalia arjuna, and Curcuma longa, with the highest UV (0.96). Curcuma longa also demonstrated the highest fidelity level (93.33%).This study highlights the rich ethnomedicinal heritage of the Garo tribes and underscores the urgent need for conservation efforts to preserve both botanical resources and the associated traditional knowledge amidst rapid cultural and environmental transitions.